2009
DOI: 10.1111/j.1440-169x.2009.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Two states of active spermatogenesis switch between reproductive and non‐reproductive seasons in the testes of the medaka, Oryzias latipes

Abstract: Seasonal change in spermatogenesis was examined in the restricted spermatogonium-type testes of a teleost, Oryzias latipes. Histological observation revealed that the number of each stage of germ cells during most of the non-reproductive season, from October to January (O-J period) was nearly half of that during the reproductive season, from May to July (M-J period), except for type B spermatogonia (B-gonia), which was actually equal. As a result, the ratio of primary spermatocytes (P-cytes) to B-gonia was rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A previous study suggested that testicular germinal epithelial cells in rodents are especially susceptible to cytotoxic drugs because testicular germinal epithelial cells have high mitotic activity 23 . Spermatogonia and spermatocytes in medaka testes also show high cell proliferative activity 25 , and this finding may be related to the induction of apoptosis in spermatogonia and spermatocytes in medaka testes exposed to MTX in the present study.…”
Section: Discussionsupporting
confidence: 58%
“…A previous study suggested that testicular germinal epithelial cells in rodents are especially susceptible to cytotoxic drugs because testicular germinal epithelial cells have high mitotic activity 23 . Spermatogonia and spermatocytes in medaka testes also show high cell proliferative activity 25 , and this finding may be related to the induction of apoptosis in spermatogonia and spermatocytes in medaka testes exposed to MTX in the present study.…”
Section: Discussionsupporting
confidence: 58%
“…In these two species and other seasonal fish, FSH seems to be more involved in early spermatogenesis comprising the spermatogonial stages and LH plays the main role during the maturing process of future sperm (10,73,74). As discussed in section "7-Day Culture of Testis Explants Requires Addition of tilPE for Maintenance of Intact Testis structure" above, an influence of FSH on spermatogonial proliferation is also reported from non-seasonal fish like medaka and zebrafish (5,26,48,49). Future studies should investigate differential transcriptional activation of steroidogenesis-related genes by LH and FSH.…”
Section: Gene Expression Of the Leydig Cell Markers Star2 And Cyp11b2mentioning
confidence: 85%
“…In zebrafish, germ cell proliferation was successfully increased by recombinant FSH under tissue culture conditions (48). Also using testis culture, the proliferation of SgA and SgB could be maintained up to 10 days in medaka by adding human FSH (49). In amphibians like the newt Cynops pyrrhogaster FSH has also been studied in regard of its role in spermatogonia proliferation.…”
Section: -Day Culture Of Testis Explants Requires Addition Of Tilpe mentioning
confidence: 99%
“…We speculate that those s-males were highly suppressed over a long time and such individuals should have low FSH plasma levels (Weltzien et al 2004, Levavi-Sivan et al 2010, Schreck 2010. FSH seems to be necessary for gonial proliferation and has antiapoptotic activity on germ line cells in fish (Ohta et al 2007, Iwasaki et al 2009, Garcia-Lopez et al 2010. …”
Section: Social Hierarchy and Spermatogenesis In D-and S-malesmentioning
confidence: 99%